Antibiotic prophylaxis prescriptions prior to dental visits in the Veterans' Health Administration (VHA), 2015–2019. (22nd November 2022) - Suda, Katie J.; Fitzpatrick, Margaret A.; Gibson, Gretchen; Jurasic, M. Marianne; Poggensee, Linda; Echevarria, Kelly; Hubbard, Colin C.; McGregor, Jessina C.; Evans, Charlesnika T.
Abstract: Objective: To determine prophylaxis appropriateness by Veterans' Affairs (VA) dentists. Design: A cross-sectional study of dental visits, 2015–2019. Methods: Antibiotics within 7 days before a visit in the absence of an oral infection were included. Appropriate antibiotic prophylaxis was defined as visits with gingival manipulation and further delineated into narrow and broad definitions based on comorbidities. The primary analysis applied a narrow definition of appropriate prophylaxis: cardiac conditions at the highest risk of an adverse outcome from endocarditis. The secondary analysis included a broader definition: cardiac or immunocompromising condition or tooth extractions and/or implants. Multivariable log-linear Poisson generalized estimating equation regression was used to assess the association between covariates and unnecessary prophylaxis prescriptions. Results: In total, 358, 078 visits were associated with 369, 102 antibiotics. The median prescription duration was 7 days (IQR, 7–10); only 6.5% were prescribed for 1 day. With the narrow definition, 15% of prophylaxis prescriptions were appropriate, which increased to 72% with the broader definition. Prophylaxis inconsistent with guidelines increased over time. For the narrow definition, Black (vs White) race, Latine (vs non-Latine) ethnicity, and visits located in the West census region were associated with unnecessary prophylaxis. Variables associated with a lower risk were older age, prosthetic joints, immunocompromising condition, and rural location. Conclusions: Of every 6 antibiotic prophylaxis prescriptions, 5 were inconsistent with guidelines. Improving prophylaxis appropriateness and shortening duration may have substantial implications for stewardship. Guidelines should state whether antibiotic prophylaxis is indicated for extractions, implants, and immunocompromised patients.